Aggressive behavior in a sample of Bucaramanga student, Colombia (Encuentros, 2016)
This research’s main objective is to analyze the prevalence of aggressive behavior in adolescent students in the city of Bucaramanga. The study was descriptive, cross-sectional design, and the Inventory of Social Skills for Teens (TISS; Teenage Inventory of Social Skills, Inderbitzen and Foster, 1992, English, Hidalgo, and Inderbitzen Méndez, 2003) was applied to evaluate the test adolescent social competence in peer relationships. This research aims to determine the frequency of aggressive adolescents from a representative sample of adolescent students from three schools in the city of Bucaramanga considering the variables gender, age and academic year. The results show that the prevalence of aggressive behavior was 16.3%. In addition, the prevalence of aggressive boys was substantially higher than girls in all ages and academic courses analysed.Keywords: aggressive behaviour; gender, age, secondary education.